Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1590/s1517-83822011000400019
|View full text |Cite
|
Sign up to set email alerts
|

Modification of c and n sources for enhanced production of cyclosporin 'a' by Aspergillus Terreus

Abstract: Most of the studies regarding cyclosporin 'A' production through fungi concentrate around Tolypocladium inflatum. This is mainly due to lower reported production of this drug in other fungi. The present study was therefore conducted to explore indigenous isolates of Aspergillus terreus for synthesis of this drug and defining a production medium for obtaining high yield of cyclosporin 'A'. For this purpose carbon and nitrogen sources were optimized for the selected best strain of A. terreus. Overall results dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…This argument is supported by a previous study in which different salts and media were used and fungi showed almost same pattern of growth as given in this study. At low concentration, the biomass increased but with increase in salt concentration decreased the biomass of Aspergillus terreus [40]. Furthermore, different salts used in media affected the biomass of Fusarium oxysporum and Aspergillus nidulans [41].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This argument is supported by a previous study in which different salts and media were used and fungi showed almost same pattern of growth as given in this study. At low concentration, the biomass increased but with increase in salt concentration decreased the biomass of Aspergillus terreus [40]. Furthermore, different salts used in media affected the biomass of Fusarium oxysporum and Aspergillus nidulans [41].…”
Section: Discussionmentioning
confidence: 98%
“…Experiments performed to investigate the role of cellulose and lactose showed freely dispersed mycelia and entangled mycelia in Trichoderma reesei [46]. Another research showed that the biomass of A. terreus is significantly affected by changes in salt concentration [40]. Furthermore, the biomass of F. oxysporum and Aspergillus nidulans is also affected by use of salts in culture media [41].…”
Section: Discussionmentioning
confidence: 99%
“…Zaleski in a fructosecontaining medium, and the culture reached the maximum between days 12 and 15 (Pessoni et al, 2015). Some studies have attempted to replace CsA-producing strains with selected Aspergillus terreus Thom (FCBP58), and the CsA yield was effectively increased by optimizing the ratio of the carbon source to the nitrogen source in the medium (Tanseer and Anjum, 2011). However, few studies have analyzed how carbon sources affect the production of secondary metabolite CsA and its producing fungal mycelium growth.…”
Section: Open Accessmentioning
confidence: 99%